POLA ASUH GIZI DAN STATUS GIZI BAYI USIA 6-12 BULAN DI WILAYAH KERJA KERJA PUSKESMAS SIRAIT KECAMATAN NAINGGOLAN KABUPATEN SAMOSIR TAHUN 2013 - Angela Parapat; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Babyhood time is as the golden period for optimal growth and development of baby. In this period, babies need to have good nutrition caring pattern such as breast feeding  and complementary feeding. This research was aimed to describe the nutritional caring pattern and the nutritional status of 6 up to 12 months infants in the poor society in the working area of Sirait Publich Health Center, Nainggolan Subdistrict, Samosir District, in 2013. This research was a descriptive survey with cross sectional approach. The population was 6 up to 12 months infants since these ages were susceptible of malnutrition. The sample  is total sampling and the respondents were the infant’s mother. Primary data include maternal identity data, the identity of the baby an infant nutrition caring pattern (breast feeding  and complementary feeding practice), obtained from interviews mothers. The infants nutritional status was obtained from the results of weighing an measuring the body’s length.The result of the research showed that the nutritional caring pattern, that is breast feeding practice, the majority was categorized as moderate and not found good breast feeding. This is because there is a lack of ASI given to babies, while the complementary feeding practise was mostly good and there is a practice of feeding with food litlle or no nutritional value. The majority of infants nutritional status, based on the indicator of weight for age was categorized as normal, but we still can find some with less weight. The majority of infants nutritional status, based on the indicator of height for age was categorized as normal. However, some babies still were short and very short. The majority of infants nutritional status, based on the indicator of weight for lenght was categorized as normal, and there were a few infants had thin. Based on the results of research, it is suggested that the management of the Healthy Center to increase the information about giving the exclusive breast feeding, how to provide and give the complementary feed, an balanced nutrition to infants.   Keywords: Nutritional Caring Pattern, Infants Nutritional Status, Poor Society